RIAU SCIENTY PERCEPTION ABOUT RIAU-KEPRI SHARIA BANK CONVERSION PROCESS - Munthe, Marabona; Winario, Mohd. (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2022)
This research is based on the statement of the Governor of Riau Province who stated his plan to convert Bank Riau-Kepri into Bank Riau-Kepri Syariah in mid-2019, but until now the conversion has not been carried out. The purpose of this study was to find out how the public's perception of the conversion of Bank Riau-Kepri into Bank Riau-Kepri-Syariah. In this paper, the author uses qualitative analysis methods, namely analysis by means of descriptive qualitative and argumentative. The results of the study show that the wants and needs of the people of Riau and outside Riau for Islamic Banks are very high, this can be seen from the questionnaire that the author distributed to respondents. Public doubts arise about the seriousness of the Riau Provincial Government towards the conversion of Bank Riau-Kepri to the totality of Bank Riau-Kepri Syariah, as a community who is aware and understands sharia, the community continues to support not only haste, but stands at the forefront to fully support the achievement of a blessed society. with the establishment of sharia in the field of muamalah.